2019
DOI: 10.1155/2019/2958021
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Polyion Multilayer Coating on NPK Fertilizer as Controlled Released Fertilizer

Abstract: Low efficiency of conventional fertilizer (quick release fertilizer) application in agricultural sectors has caused environmental pollution and health problems. A method to overcome the drawback of the conventional fertilizer is by controlled release fertilizer (CRF) preparation. CRF is expected to be able to fulfil the nutrient demand of targeted plants. The objective of this research is to prepare CRF by coating NPK fertilizer with multilayer chitosan-polyanion using alginate, pectin, and sodium tripolyphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Therefore, it can be concluded that chitosan as binder was able to decrease the nitrogen release rate of the prepared fertilizer. This result can also be compared to a previous experiment reported by Kusumastuti et al (2019) The simulation result of nitrogen release with some empirical equation is shown in Figure 5 where the constant value is shown in Table 3. From Figure 5 a, b and c, the nitrogen release data follow the diffusion-relaxation and diffusion-erosion model rather than zero order kinetic model.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Therefore, it can be concluded that chitosan as binder was able to decrease the nitrogen release rate of the prepared fertilizer. This result can also be compared to a previous experiment reported by Kusumastuti et al (2019) The simulation result of nitrogen release with some empirical equation is shown in Figure 5 where the constant value is shown in Table 3. From Figure 5 a, b and c, the nitrogen release data follow the diffusion-relaxation and diffusion-erosion model rather than zero order kinetic model.…”
Section: Introductionmentioning
confidence: 56%
“…Furthermore, the application of inorganic fertilizer needs high-cost labor due to several times of fertilization usage in one cycle of planting periods (Zhang et al, 2018). França et al, 2018;Jannoura et al, 2014;Kusumastuti et al, 2019;Wang et al, 2018;Zhao et al, 2016 -Zahrani, 1999;Purnomo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan is one of the biobased materials which has a high potential to be used as a matrix in the slow-release fertilizer. Multilayer chitosan mixed with alginate, pectin, and sodium tripolyphosphate (TPP) produced a nitrogen release controlling mechanism (Kusumastuti et al, 2019). Chitosan blended with montmorillonite clay (MMt) microparticles were capable to maintain the concentration of the potassium release in the soil (Messa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming demand for food in line with the ever-increasing global population has given rise to additional exploration to produce sufficient food with sustainable agriculture to satisfy consumers' current nutritional needs (Zhang et al 2017). Fertilisers are crucially important for delivering nutrients to plants to produce high-quality crops for food security (Kusumastuti et al 2019). Similarly, pesticides are chemicals used to eliminate pests and pathogens.…”
mentioning
confidence: 99%